Philosophical-social analyse of fears: ontogenesis, phylogenesis and theory of structuration - Durmanenko, Alexander; Дурманенко, Олександр (Східноєвропейський національний університет імені Лесі Українки, 2016)
The article analyzes the phenomenon of modern social risks and fears, as matches a certain state of social development.
Філософсько-соціальний аналіз страхів: онтогенез, філогенез і теорія структурації
Keywords: social structure; соціальна структура; fears; страхи; risks; ризики; ontogenesis; онтогенез; phylogenesis; філогенез; structuration; структурування